Digitalization And Smart Operations As Drivers Of Business Performance And Work Life Balance Among Mompreneurs In Makassar - Maghfirah Sari Azis; Anendha Destantyo Nugroho (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study investigates how digitalization and smart operations influence business performance and work–life balance among mompreneurs in Makassar, Indonesia. The rapid growth of digital platforms has opened opportunities for women entrepreneurs, yet many still face challenges in managing time, operational efficiency, and family responsibilities simultaneously. Therefore, this research aims to analyze how digital adoption and operational discipline contribute to both entrepreneurial success and personal well-being. The study employs a sequential explanatory mixed-method design, beginning with quantitative analysis of 154 survey responses using reliability testing and Partial Least Squares Structural Equation Modeling (PLS-SEM), followed by qualitative interviews with ten mompreneurs to capture practical insights. The quantitative findings reveal that digitalization and smart operations significantly and positively affect business performance (β = 0.46 and 0.31, p < 0.001) and work–life balance (β = 0.50 and 0.32, p < 0.001), with R² values of 0.457 and 0.449, respectively. The qualitative analysis supports these results, showing that digital tools such as online marketplaces, QR-based payments, and social media marketing enhance flexibility, confidence, and family collaboration. The synthesis of both phases confirms that digitalization and smart operations function as complementary enablers of inclusive and sustainable entrepreneurship for women. The study concludes that strengthening digital literacy, improving process discipline, and fostering peer mentoring can help mompreneurs achieve higher productivity while maintaining family harmony.